PHOTOREACTION OF a, B - ENONES IN METHANOL IN THE PRESENCE OF TITANIUM (IV) CHLORIDE - P. Lotulung; T. Sato (Research Center for Chemistry - LIPI, 1992)
When cyclic a, B-unsaturated carbonyl compounds were irradiated by ultraviolet from a high pressure mercury vapour lamp at 25 °C, in alcohols in the presence of titanium chloride, a coupling reaction between the carbonyl carbon atom and the a-carbon atom of the alcohol took place, producing dihydrofurans, monomethylether, acetals or aldehides, but in the case of a-methyl substituted enone it resulted in diol monomethylether due the two times occuring methanol substitution.